ANALISIS PPENGARUH CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP NET INTEREST MARGIN - B31107007, Suyanto (Jurnal Manajemen Update, 2013)
As intermediary institution in finance, banks has important role in business especially when they deal with the loan reserves that are used for investment and capital working. The measurement of banking capacity to get income from loan interest is in the form of Net Interest Margin (NIM). NIM performance can be influenced by many factors, in this research the factors that will be tested are Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR). This research aimed to know, the growth of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) and also to analyze whether capital performance (Capital Adequacy Ratio) and liquidity (Loan to Deposit Ratio) simultaneously and partially influence Net Interest Margin (NIM) or not. The samples were taken by using purposive judgement sampling so that six years research period can be obtained. The period was begun from 2006 until 2011 and covered twelve conventional state banks and private banks. The data is then analyzed by using multiple linear regressions which previously had undergone the classical assumption test. The research shows that commonly CAR decreases while LDR and NIM have positive growth. CAR, LDR, and NIM of conventional private and state banks are in a good performance. The regression result shows that Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) simultaneously influence NIM but partially only Loan to Deposit Ratio (LDR) which has significant influence towards Net Interest Margin (NIM). The correlation between independent variables (CAR and LDR) with dependent variable (NIM) is strong enough. Simultaneously independent variables can explain the changes in NIM of 50,6% while the rest can be explained by other variables which are not tested in this research.